2014
DOI: 10.1093/nar/gku421
|View full text |Cite
|
Sign up to set email alerts
|

An RNF168 fragment defective for focal accumulation at DNA damage is proficient for inhibition of homologous recombination in BRCA1 deficient cells

Abstract: The E3 ubiquitin ligase RNF168 is a DNA damage response (DDR) factor that promotes monoubiquitination of H2A/H2AX at K13/15, facilitates recruitment of other DDR factors (e.g. 53BP1) to DNA damage, and inhibits homologous recombination (HR) in cells deficient in the tumor suppressor BRCA1. We have examined the domains of RNF168 important for these DDR events, including chromosomal HR that is induced by several nucleases (I-SceI, CAS9-WT and CAS9-D10A), since the inducing nuclease affects the relative frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 55 publications
2
29
0
Order By: Relevance
“…We hypothesized that the predicted 5′ overhang structure could be processed to yield a recombination favourable 3′ overhang. If this were the case, GC would be sensitive to an ectopically expressed 3′–5′ exonuclease such as TREX2 known to process 3′ overhangs282930. Indeed, co-expression of TREX2 and D10A Cas9 resulted in a strong reduction in GC frequency, indicating that a 3′ overhang is part of the life cycle of a 5′ overhang undergoing GC independent of the gRNA pair (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…We hypothesized that the predicted 5′ overhang structure could be processed to yield a recombination favourable 3′ overhang. If this were the case, GC would be sensitive to an ectopically expressed 3′–5′ exonuclease such as TREX2 known to process 3′ overhangs282930. Indeed, co-expression of TREX2 and D10A Cas9 resulted in a strong reduction in GC frequency, indicating that a 3′ overhang is part of the life cycle of a 5′ overhang undergoing GC independent of the gRNA pair (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…This reporter assay typically involves using I-SceI to induce the DSB, but, to remain consistent across assays, we used an sgRNA to target Cas9 to the I-SceI site in DR-GFP (Supplemental Fig. S2), as described previously (Munoz et al 2014). We found that expression vectors for 3xf-NLS-BRC3 and RAD51-K133R, compared with control empty vector (EV), each caused a substantial decrease in HDR ( Fig.…”
Section: Rmds At Dsb/repeat Distances ≥33 Kb Are Inhibited By Rad51 mentioning
confidence: 84%
“…In addition to the classic role of RNF8 described above, other effects of RNF8 have been reported. Studies have confirmed that RNF8 depletion partially suppresses HR defects caused by BRCA1 depletion, and the degree of HR suppression due to RNF8 depletion is significantly less than that due to RNF168 depletion . Moreover, scientists revealed a newly discovered non‐catalytic role of RNF8 in unfolding higher‐order chromatin structures .…”
Section: Introductionmentioning
confidence: 95%
“…Studies have confirmed that RNF8 depletion partially suppresses HR defects caused by BRCA1 depletion, and the degree of HR suppression due to RNF8 depletion is significantly less than that due to RNF168 depletion. 15 Moreover, scientists revealed a newly discovered non-catalytic role of RNF8 in unfolding higher-order chromatin structures. 16 Furthermore, RNF8 has been shown to promote cellular resistance to replication stress and is important for meiosis.…”
mentioning
confidence: 99%